Construction of conductive multilayer films of biogenic triangular gold nanoparticles and their application in chemical vapour sensing - Singh, Amit; Chaudhary, Minakshi V.; Sastry, Murali (Nanotechnology, 2006)
Metal nanoparticles are interesting building blocks for realizing films for a number of applications that include bio- and chemical sensing. To date, spherical metal nanoparticles have been used to generate functional electrical coatings. In this paper we demonstrate the synthesis of electrically conductive coatings using biologically prepared gold nanotriangles as the building blocks. The gold nanotriangles are prepared by the reduction of aqueous chloroaurate ions using an extract of the lemongrass plant (Cymbopogon flexuosus) which are thereafter assembled onto a variety of substrates by simple solution casting. The conductivity of the film shows a drastic fall upon mild heat treatment, leading to the formation of electrically conductive thin films of nanoparticles. We have also investigated the possibility of using the gold nanotriangle films in vapour sensing. A large fall in film resistance is observed upon exposure to polar molecules such as methanol, while little change occurs upon exposure to weakly polar molecules such as chloroform.